MICROMEGAS PERFORMANCE BASED IN ARGONISOBUTANE AND ARGON-DEMETHYL-ETHER - Hamid Mounir; Mustapha Haddad; Seddik Bri (European Scientific Journal, ESJ, 2014)
MICROMEGAS (MICROMEsh GAs Structure) detector which is among the major families of position detectors in High Energy Physics, introduced in the late sixties, detects and localizes energy deposit by charged particles over large areas, is widely used in particle physics. This detector is in a sealed in which mixture gas circulates. This mixture usually based, on a noble gas and a few proportions a “quencher”. In this paper, we use 55Fe source that produces X-ray photons of 5.9 keV and a mixture gas on Argon (Ar) with quencher as isobutane (iC4H10) and dimethyl-Ether. We will present the results of the MATLAB simulations of MICROMEGAS performance taking into account all the processes from the primary ionization, the distribution of charges in the electrodes and the electron avalanche amplification (first Townsend coefficient and amplification gain). All the simulated results obtained indicate that the performances of the detector depend on many parameters. The simulation results are nearly consistent with the data that are published in other references, and provide important information in the MICROMEGAS design, making and operating. Our simulation predicts that further improvements are still possible for give a best spatial and temporal resolution for a MICROMEGAS detector.